Strategi Komunikasi Pemilik Kucing Selebriti dalam Membangun Personal Branding - Nurkholis Majid; Suzy S. Azeharie (Kiwari, 2023)
In this study, we analyze the communication strategy for using social media TikTok as a forum for building a personal branding for a celebrity cat owner on the TikTok account @kingvodkagentolet. Personal branding is important for a celebrity to be able to maintain a characteristic that can always be remembered by the public. Therefore, one of the communication strategies helps to maximize the formation of the branding that he builds. The communication strategy is important to be able to communicate the messages conveyed by these celebrities so that the public recognizes them as individuals who have good personal branding. TikTok is an entertainment social media as a means of self-expression for celebrity cat owners to upload all their daily activities with their cats so that this is considered entertaining by the public. Therefore, the purpose of this study is to find out how the communication strategies used by celebrity cat owners can make their cats famous and many big brands invite collaboration through them. This study uses qualitative research methods, with social media theory, TikTok, TikTok celebrities, authentic personal branding, and the circular model of SoMe for Social communication strategy. From the results of the analysis of this study, it is felt that using the TikTok application is easier to get engagement than other applications, the use of TikTok also helps to be recognized by the public more quickly so that it can be said that the use of the TikTok application is considered more effective in getting a wide reach by the owner of a celebrity cat, namely Angelia Dinata. Dalam penelitian ini menganalisis strategi komunikasi penggunaan media sosial TikTok sebagai wadah untuk membangun sebuah personal branding pada seorang pemilik kucing selebriti pada akun TikTok @kingvodkagentolet. Personal branding penting bagi seorang selebriti untuk bisa mempertahankan ciri khas untuk bisa selalu diingat oleh khalayak. Oleh karena itu salah satu strategi komunikasi membantu untuk memaksimalkan pembentukan branding yang ia bangun. Strategi komunikasi merupakan hal penting untuk bisa mengkomunikasikan pesan yang disampaikan oleh selebriti tersebut sehingga khalayak mengenali sebagai individu pemilik personal branding yang baik. TikTok adalah salah satu media sosial hiburan sebagai sarana ekspresi diri sang pemilik kucing selebriti untuk mengunggah segala aktivitas keseharian bersama kucingnya sehingga hal tersebut dinilai menghibur oleh khalayak. Oleh karena itu tujuan dari penelitian ini ialah mengetahui bagaimana strategi komunikasi yang digunakan oleh sang pemilik kucing selebriti untuk bisa membuat kucingnya menjadi terkenal dan banyak jenama besar yang mengajak kerja sama melalui dirinya. Penelitian ini menggunakan metode penelitian kualitatif, dengan teori media sosial, TikTok, selebriti TikTok, authentic personal branding, dan strategi circular model of SoMe for Social communication.